2020
DOI: 10.21891/jeseh.705145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Problem-based Learning on 7th-grade Students’ Environmental Knowledge, Attitudes, and Reflective Thinking Skills in Environmental Education

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
10
0
4
Order By: Relevance
“…This is consistent with the findings of Esen and Neş'e (2014) found that the creative skills of students increased after learning through PBL. Evrim and Guzide (2020) found that students who are taught by PBL had the environmental knowledge scores higher than before learning and consistent with the findings of Supala, Poonsuk, and Thawatchai (2009) found that the students who were taught using the question-based teaching method combined with the question-based techniques have academic achievement in science after study higher than before study. So, it showed that learning activities on waste and sewage management using question and problems-based learning is appropriate and resulting in the advancement of learning.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the findings of Esen and Neş'e (2014) found that the creative skills of students increased after learning through PBL. Evrim and Guzide (2020) found that students who are taught by PBL had the environmental knowledge scores higher than before learning and consistent with the findings of Supala, Poonsuk, and Thawatchai (2009) found that the students who were taught using the question-based teaching method combined with the question-based techniques have academic achievement in science after study higher than before study. So, it showed that learning activities on waste and sewage management using question and problems-based learning is appropriate and resulting in the advancement of learning.…”
Section: Discussionsupporting
confidence: 85%
“…According to Suhadi et al (2019), real problems can help students determine the environmental causes and impacts to raise or improve environmental attitudes. PBL, which invites students to observe, see problems directly, discussion, and questionanswer, also plays an essential role in improving students' environmental attitudes (Husnah et al, 2017;Sueb et al, 2020;Ural & Dadli, 2020). The module's analysis and evaluation section also plays an important role because, through this activity, students re-evaluate their performance in solving problems to increase student awareness to care more about the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing of population growth, industrialization, shortage, and in some cases, the destruction of natural resources (1,2), have made human beings to think about and reflect on the type and manner of their interaction with the environment (3,4). In order to have a proper management system, measurement tools should be created (5).…”
Section: Introductionmentioning
confidence: 99%